2008
DOI: 10.1007/s00264-008-0699-4
|View full text |Cite
|
Sign up to set email alerts
|

Five-year DEXA study of 88 hips with cemented femoral stem

Abstract: We performed repeated dual-energy X-ray absorptiometry (DEXA) measurements over five years in a homogeneous patient population to study the effect of a cemented stem on proximal femoral bone remodelling. Data from 88 patients (88 hips) implanted with total hip arthroplasty (THA) prostheses were extracted from three randomised studies. Femoral bone mineral density (BMD) was measured using a Lunar DPX-IQ densitometer for five years postoperatively. At one year the BMD changes had decreased between −2.0% [region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The negative correlation between BMD and aging is well documented [22]. Further, positive correlation between BMD and body weight was reported [17,18]. Yamauchi et al reported that leptin directly stimulates osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The negative correlation between BMD and aging is well documented [22]. Further, positive correlation between BMD and body weight was reported [17,18]. Yamauchi et al reported that leptin directly stimulates osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies demonstrated a relationship between BMD and HHS, age or BMI [17][18][19]. Korovessis demonstrated no correlation between age and periprosthetic BMD changes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data suggests that a condition close to homeostasis is established after 2-3 years for both cemented [2,3,40] and cementless total hip replacements [20,41,42], with slight changes at 5-7 years. Therefore, the time constant (T) was fitted such that 90% of the BMD change in the most active Gruen Zone, 7, had completed at 2 years (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…As such, all levels of risk factors would be provide more merit for the efficacy of proactive intervention of bisphosphonates similar to what the original bisphosphonate literatures depicted. [7,16,19] Therefore, no control over BMD was used to represent a more real world cross section of what a typical trauma practice would see in an emergency room where BMD's are simply unavailable. The study protocol received full approval from Institutional Review Board, Patient Advocacy Council, Inc.…”
Section: Methodsmentioning
confidence: 99%
“…However, clinical evidence suggests that the short-term gains of bisphosphonate therapy may not be sustained in the long term or reversed once they have occurred. [17,19,20,21] Although the benefits of risedronate administration on enhancing periprosthetic BMD have been observed in the first year post-THA, currently, there is no evidence to show that the risedronate therapy may reverse the delayed periprosthetic bone loss occurring after the initial post-operative year. We hypothesized that oral risedronate may augment or prevent bone loss in well osteointegrated patients following THA, just as it has been demonstrated in recent postoperative THA patients.…”
Section: Introductionmentioning
confidence: 99%